Vaccine-Induced Immunological Memory in Invasive Fungal Infections – A Dream so Close yet so Far - Biswas, Partha S. (Frontiers in Immunology, 2021)
It is estimated that about 1.5 million people die due to invasive fungal infections (IFIs) every year worldwide. Most of the IFIs are caused by Candida, Aspergillus and Cryptococcus species. Lack of approved vaccines and the emergence of antifungal drug-resistant strains pose major constraints in controlling IFIs. A comprehensive understanding of the host immune response is required to develop novel fungal vaccines to prevent death from IFIs. In this review, we have discussed host-pathogen interaction in shaping immunological memory and development of long-term protective immunity to IFIs and challenges associated with the development of approved antifungal vaccines. Further, we emphasized the role of long-lived memory cells in protection against subsequent infections and summarized the available information on the current vaccine strategies.